Accurate Real-Time Occupant Energy-Footprinting in Commercial Buildings - Cheng, Yun; Chen, Kaifei; Zhang, Ben; Liang, Chieh-Jan Mike; Jiang, Xiaofan; Zhao, Feng (BuildSys (ACM Workshop On Embedded Systems For Energy-Efficient Buildings), 2012)
Buildings consume a significant portion of the total delivered energy. While the community has been working on monitoring the building energy usage, we argue that an accurate accounting of individual occupants’ energy expenditure in real-time is still the missing piece. And, this missing piece makes incentivizing energy reduction a challenge. We take a systematic approach and identify the lack of real-time association between human actions and observed energy consumption as one roadblock. To this end, we first present a model that enables real-time accounting of appliances with delay characteristics. Building on top of this model, we introduce a complete system that fairly attributes energy usages of shared resources, and reveals per-person energy footprint information. And, our system has several ways to analyze and visualize individuals’ energy footprint. Finally, we present the deployment experience at an office building.